Cognitive functions in elite and sub-elite youth soccer players aged 13 to 17 years - Huijgen, B. C. H.; Leemhuis, S.; Kok, N. M.; Verburgh, L.; Oosterlaan, J.; Elferink-Gemser, M. T.; Visscher, C. (PLOS ONE, 2015)
Soccer players are required to anticipate and react continuously in a changing, relatively unpredictable situation in the field. Cognitive functions might be important to be successful in soccer. The current study investigated the relationship between cognitive functions and performance level in elite and sub-elite youth soccer players aged 13-17 years. A total of 47 elite youth soccer players (mean age 15.5 years, SD = 0.9) and 41 sub-elite youth soccer players (mean age 15.2 years, SD = 1.2) performed tasks for "higher-level" cognitive functions measuring working memory (i.e., Visual Memory Span), inhibitory control (i.e., Stop-Signal Task), cognitive flexibility (i.e., Trail Making Test), and metacognition (i.e., Delis-Kaplan Executive Function System Design Fluency Test). "Lower-level" cognitive processes, i.e., reaction time and visuo-perceptual abilities, were also measured with the previous tasks. ANOVA`s showed that elite players outscored sub-elite players at the "higher-level" cognitive tasks only, especially on metacognition (p < .05). Using stepwise discriminant analysis, 62.5% of subjects was correctly assigned to one of the groups based on their metacognition, inhibitory control and cognitive flexibility performance. Controlling for training hours and academic level, MANCOVA`s showed differences in favor of the elite youth soccer players on inhibitory control (p = .001), and cognitive flexibility (p = .042), but not on metacognition (p = .27). No differences were found concerning working memory nor the "lower-level" cognitive processes (p > .05). In conclusion, elite youth soccer players have better inhibitory control, cognitive flexibility, and especially metacognition than their sub-elite counterparts. However, when training hours are taken into account, differences between elite and sub-elite youth soccer players remain apparent on inhibitory control and cognitive flexibility in contrast to metacognition. This highlights the need for longitudinal studies to further investigate the importance of "higher-level" cognitive functions for talent identification, talent development and performance in soccer.